2009
DOI: 10.1007/s10853-008-3166-0
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analyses of syntactic foam behaviour in deepwater environment

Abstract: Over the past 10 years, numerous studies were performed to better understand the behaviour of the glass syntactic foams used as thermal insulation of pipes for deepwater production. The obtained results outlined some specific behaviour of polymeric syntactic foams reinforced by glass microballoons in service conditions: both water uptake and mechanical stress have a key impact on thermal properties. This article focuses first on the wet behaviour of glass syntactic foams. The effect of water is investigated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…They observed that the moisture absorption of 40% in syntactic foam over a period of 18 months in deionized water between 20 C and 120 C resulted in increased electrical conductivity with mass gain. Grosjean et al 26 observed the moisture absorption behavior of syntactic foams up to 400 days in different environmental conditions such as deionized water, sea water, and high humidity at 80 C. They reported that maximum weight gain at 80 C ranged from 1% to 16% depending on environment. Sadler et al [27] studied the moisture absorption behavior of cenosphere/phenolic syntactic foams (eco-core) in sea and tap water at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the moisture absorption of 40% in syntactic foam over a period of 18 months in deionized water between 20 C and 120 C resulted in increased electrical conductivity with mass gain. Grosjean et al 26 observed the moisture absorption behavior of syntactic foams up to 400 days in different environmental conditions such as deionized water, sea water, and high humidity at 80 C. They reported that maximum weight gain at 80 C ranged from 1% to 16% depending on environment. Sadler et al [27] studied the moisture absorption behavior of cenosphere/phenolic syntactic foams (eco-core) in sea and tap water at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…They have been widely used in several engineering applications due to their low moisture absorption, good thermal insulation, and excellent strength to weight ratio, vibration isolation, and low radar cross-section properties [3][4][5]. As a class of advanced lightweight composites, syntactic foams have been widely employed in more and more engineering applications, e.g., civil, automobile, aeronautical, marine equipment for deep sea operations [6], aircraft components, spacecraft solid rocket booster nose cones fillings, thermal insulation for deep sea pipelines [7][8][9], core materials of sandwiches [10,11], and structural components in aerospace industry [12].…”
Section: Introductionmentioning
confidence: 99%
“…Syntactic foams, which are made of hollow glass microspheres embedded in a polymer matrix, are becoming more widely used for thermal insulation of offshore pipelines and bundles which convey oil and gas resources from extraction sites located in deep water [1], [2], [3], [4], [5], [6], [7], [8], [9], [10], [11] and [12]. Insulation material durability contributes directly to the maintenance of reliable offshore production (flow assurance) over 20 years of service.…”
Section: Introductionmentioning
confidence: 99%